Anatomical analysis of peach palm (Bactris gasipaes) leaves cultivated in vitro, ex vitro and in vivo - Batagin-Piotto,Katherine Derlene (2012)
The present work characterized and compared the anatomical structures of the leaves of Bactris gasipaes (Arecaceae) plants grown under different cultivation conditions (in vitro, ex vitro and in vivo) with the goal of identifying the origins of the difficulties encountered in acclimatizing micro-plants. The Quant program was used to determine leaf tissue thicknesses and areas, and histochemical tests were performed on leaf sections and analyzed using light microscopy. Stomatal and trichome densities were determined using the epidermal impression method and by scanning electronic microscopy. Our results indicated that there were no discernible alterations of the anatomical characteristics of the leaves of micro-plants cultivated under differing conditions and that the thickening of the mesophyll and the vascular fibers indicated adaptive responses to ex vitro conditions. As such, the observed difficulties in acclimatizing peach palm micro-plants to ex vitro conditions cannot be attributed to plant anatomical characteristics acquired during in vitro cultivation.